Stratospheric injection of solid particles reduces side effects on circulation and climate compared to SO2 injections - Stefanetti, Fabrice; Vattioni, Sandro; id_orcid:0 000-0002-4099-3903; Dykema, John A.; Chiodo, Gabriel; id_orcid:0 000-0002-8079-6314; Sedlacek, Jan; Keutsch, Frank N.; Sukhodolov, Timofei (IOP Publishing, 2024)
Most research of stratospheric aerosol injection (SAI) for solar radiation modification has focused on injection of SO₂. However, the resulting sulfuric acid aerosols lead to considerable absorption of terrestrial infrared radiation, resulting in stratospheric warming and reduced cooling efficiency. Recent research suggests that solid particles, such as alumina, calcite or diamond, could minimize these side effects. Here we use, for the first time, the atmosphere-ocean-aerosol-chemistry-climate model SOCOLv4.0, incorporating a solid particle scheme, to assess the climatic impacts of SAI by these injection materials. For each substance, we model tropical SAI by means of constant yearly injection of solid particles, aimed to offset the warming induced by a high-GHG emission scenario over the 2020-2100 period by 1 K. We show that solid particles are more effective than sulfur at minimising stratospheric heating, and the resulting side-effects on the general atmospheric circulation, stratospheric moistening, and tropopause height change. As a result, solid particles also induce less residual warming over the arctic, resulting in greater reduction of GHG-induced polar amplification compared to sulfuric acid aerosols. Among the materials studied here, diamond is most efficient in reducing global warming per unit injection, while also minimizing side effects. ISSN:2752-5295